Resource Reallocation of Two Grass Species During Regrowth After Defoliation - Liu, Yanshu; Yang, Xiaohui; Tian, Dashuan; Cong, Richun; Zhang, Xiao; Pan, Qingmin; Shi, Zhongjie (Frontiers in Plant Science, 2018)
Defoliation is widely used for grassland management. Our understanding of how grass species adjust their regrowth and regain balance after defoliation remains limited. In the present study, we examined the regrowth processes of two dominant species after defoliation in Inner Mongolia grasslands. Our results showed that the aboveground biomass and total biomass of both species significantly decreased and did not completely recover to the control level after 30 days of regrowth. The leaf mass ratio (LMR) of Leymus chinensis reached the control level at 15 days, but that of Stipa grandis did not recover to the control level. The root mass ratio (RMR) of these species reached the same levels as that of the control plants within 10 days after defoliation. As indicated by the dynamics of water-soluble carbohydrates (WSCs), protein, and biomass-based shoot: root ratios, both species regained balances of WSCs and protein between above- and belowground organs at day 10 after defoliation; however, the biomass regained balance at day 15 after defoliation. We deduced that the biomass-based shoot: root ratio was regulated by the WSCs and protein concentrations. In conclusion, following defoliation, both grass species first restore their nutrient-based balance between above- and belowground parts and then regain biomass balance.